Beiträge zur Insektenfauna der DDR: Lepidoptera - Pterophoridae. - Sutter, Reinhard (Contributions to Entomology = Beiträge zur Entomologie, 1991)
In the GDR 56 species of the Pterophoridae have been established. Eight species are not evident from 1950 and before. From all species have been copied the wings and the male and female genitals. In the key have been used the separation of species on the scaled of abdomen.